House consolidation in Tondo - Reforma, Mila A. (1981)
The physical environment of Tondo is changing at a dramatic pace. Two-story structures built out of concrete and wood are now visually, perhaps, the most conspicious and characteristic feature of the area. The physical components of the project, particularly the introduction of infrastructure and utilities, have been directly responsible for the dramatic transformation of the overall Tondo environment. The change, however, has acted as a powerful stimulant for individual families to undertake equally large-scale improvements in the quality of their structure. By all current indications, the residents of Tondo are validating the assumption that the solution to the squatter problem lies in a policy based upon the provision of the elements of environmental security - appropriate locations, tenancies and investment opportunities - rather than on the direct construction of houses. The results of a study that measures the changes in housing characteristics of Tondo families indicate that not only are the residents investing resources for improvements, but are doing so at a rate reflective of the pacing of the project and at a greater extent than families living elsewhere. But even as the success of the Tondo project is being documented, the relatively novel approaches used have raised a few issues that require examination for purposes of applying the same concepts in other slum and squatter settlements in the country. Foremost of these issues include the need to examine the appropriateness of (1) lot sizes being awarded; (2) the emphasis being given to the objective of minimum dislocation of structures; (3) level of services being provided; and (4) the Housing Materials Loan Program.
Keywords: Public housing aspects -- Tondo (Manila); Squatter settlements -- Tondo (Manila); Housing rehabilitation